PESAN-PESAN DAKWAH DALAM NOVEL MENGEJAR CINTA HALAL KARYA PRIMA MUTIARA (KAJIAN ANALISIS ISI) - Siti Iklima Asri; Sainil Amral; Harbeng Masni (Universitas Batanghari, 2021)
This research aims to describe the messages of da'wah in the novel Mengejar Cinta Halal by Prima Mutiara about aspects of aqidah consisting of five elements, namely faith in Allah SWT, belief in angels, belief in the Books, faith in the prophets, faith in Qadha and Qadar. This research includes a type of descriptive research that is qualitative with a structural approach. The data in this study is verbal data in the form of words, dialogues and sentences in the form of paragraphs, both containing the messages of da'wah contained in the novel Mengejar Cinta Halal by Prima Mutiara. Furthermore, the conclusions are listed each of the problems in the form of quotations contained in the novel. From the results of the research can be concluded that in the novel Mengejar Cinta Halal by Prima Mutiara, there are 54 quotations on aspects of aqidah, the details of which are faith in Allah SWT of 43 quotations, faith in angels is 1 quotation, faith in the Books is 4 quotations. Moreover faith in the Apostles are not found, and faith in Qadha and Qadar is 6 quotations.